The Impact of Anxiety and Depression on Individuals with Smoking Habit - Utami, Dian Cahaya (HM Publisher, 2023)
Anxiety and depressive disorder is a prevalent mental health disorder on a global scale, often exhibiting a high comorbidity rate with smoking behavior. This present review offers a comprehensive narrative synthesis of the latest scholarly studies pertaining to the influence of anxiety and depression on the onset, perpetuation, and cessation of smoking behavior. The existing literature exhibits variability in terms of the evidence supporting the association between anxiety or anxious symptoms and smoking behavior. The findings consistently indicate a significant association between anxiety and smoking, suggesting a high comorbidity rate between these two illnesses. The existing literature on the association between anxiety, depression and various factors such as onset, severity indicators, and cessation outcomes has yielded inconsistent findings. While there exists compelling data supporting the association between smoking and anxiety, notable distinctions may be observed regarding the specific impact of anxiety on the beginning, severity, and quitting outcomes of smoking. In the future, it will be necessary to employ more advanced approaches in order to ascertain causative relationships, as well as potential moderators and mediators, within the association between anxiety, depression and smoking habit.